2020
DOI: 10.46497/archrheumatol.2021.7534
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Fibromyalgia and Metabolic Syndrome in Females: The Effects on Fatigue, Clinical Features, Pain Sensitivity, Urinary Cortisol and Norepinephrine Levels: a Cross-sectional Study

Abstract: Objectives This study aims to evaluate the coexistence of metabolic syndrome (MetS) and fibromyalgia syndrome (FMS) and determine the effects of this coexistence on neuroendocrine levels and clinical features of FMS. Patients and methods One-hundred female FMS patients (mean age 40.1±7.8 years; range, 24 to 58 years) and 38 healthy females (mean age 40.4±5.8 years; range, 30 to 55 years) were included in this cross-sectional study. MetS was identified by using the crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…However, the data on norepinephrine were very heterogeneous, with studies reporting increased norepinephrine levels 1,34 as well as studies showing decreased norepinephrine levels. 33,55,63,84 Predominantly studies with wide confidence intervals showed increased levels, 6,18,57,82 indicating higher uncertainty of the estimate, whereas studies with narrower confidence intervals tended to show reduced levels, 8,33,55,63,82 usually indicating more precise estimates. The idea of an increased sympathetic tone in individuals with FMS has therefore been extended by the hypothesis of an inadequate norepinephrine synthesis in individuals with FMS as a result of chronic stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the data on norepinephrine were very heterogeneous, with studies reporting increased norepinephrine levels 1,34 as well as studies showing decreased norepinephrine levels. 33,55,63,84 Predominantly studies with wide confidence intervals showed increased levels, 6,18,57,82 indicating higher uncertainty of the estimate, whereas studies with narrower confidence intervals tended to show reduced levels, 8,33,55,63,82 usually indicating more precise estimates. The idea of an increased sympathetic tone in individuals with FMS has therefore been extended by the hypothesis of an inadequate norepinephrine synthesis in individuals with FMS as a result of chronic stress.…”
Section: Discussionmentioning
confidence: 99%
“…5,71 Existing studies show contradictory patterns. Although some studies report an HPA-axis upregulation with increased levels of plasma cortisol, 8 others suggest HPA-axis suppression with reduced cortisol levels 19 in individuals with FMS compared with controls. The same inconsistency can be found on data of SAM dysregulation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…111 This study found a significantly higher proportion of FM with a systolic blood pressure ≥130 mm Hg. Most studies report high prevalence of Metabolic syndrome (MetS) in FM, [112][113][114] which is associated with increased risk for cardiovascular disease, diabetes mellitus, and all-cause mortality. 113,115 The increased VAT, ASAT, liver fat, and BMI together with nearly a third of the patients displaying systolic hypertension may indicate that this FM cohort had increased prevalence of MetS.…”
Section: Discussionmentioning
confidence: 99%